Americans with Disability Act (ADA) and Associational Discrimination: Policy and Practice Issues for Employers - Calvasina, Gerald E.; Calvasina, Richard V.; Calvasina, Eugene J. (Journal of Organizational Psychology, 2017)
The associational discrimination provision of the Americans with Disability Act (ADA) prohibits employment discrimination against applicants and employees, whether or not they have a disability, because of their known relationship or association with a person with a known disability. Over the last ten years, the number of charges alleging violation of the association provisions received by the Equal Employment Opportunity Commission (EEOC), with the exception of FY 2012, has steadily increased. The purpose of this paper is to examine recent litigation associated with the associational discrimination provisions of the ADA and present suggestions to help employers minimize litigation risks.